2018
DOI: 10.1080/1068316x.2018.1503664
|View full text |Cite
|
Sign up to set email alerts
|

The multifinality of vulnerability indicators in lone-actor terrorism

Abstract: To move beyond current aggregate and static conclusions regarding radicalisation and subsequent terrorist behaviour, empirical research should look to criminological models which are influenced by the life course perspective.Current UK government policy designed to prevent radicalisation and terrorist engagement look to outputs from criminological perspectives to inform policy and practice. However, the guidance suffers from a lack of specificity as to the major concept of 'vulnerability to radicalisation', an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 71 publications
3
63
0
Order By: Relevance
“…Other studies support in various ways the model of the TRAP‐18, highlight its potential weakness, such as an absence of protective factors, and also suggest directions for future research. Corner et al () demonstrated the usefulness and importance of time sequence analysis in a large sample of lone actor terrorists, as we have noted. Schuurman, Bakker, Gill, and Bouhana () found that lone actor terrorists are generally poor at operational security, leak their intent in various ways over the course of weeks and months – as do most targeted violence attackers (Silver, Simons, & Craun, ) – and have broader social contacts than was originally surmised.…”
Section: Discussionsupporting
confidence: 73%
“…Other studies support in various ways the model of the TRAP‐18, highlight its potential weakness, such as an absence of protective factors, and also suggest directions for future research. Corner et al () demonstrated the usefulness and importance of time sequence analysis in a large sample of lone actor terrorists, as we have noted. Schuurman, Bakker, Gill, and Bouhana () found that lone actor terrorists are generally poor at operational security, leak their intent in various ways over the course of weeks and months – as do most targeted violence attackers (Silver, Simons, & Craun, ) – and have broader social contacts than was originally surmised.…”
Section: Discussionsupporting
confidence: 73%
“…Lone‐actor terrorists were also significantly more likely to display low self‐control and thrill‐seeking behaviors, as found by Nussio , as well as proxy indicators of a crime‐ and/or violence‐supportive morality, such as having a history of substance abuse, having a criminal conviction and/or experiencing imprisonment, violence unrelated to terrorism, and escalating levels of anger. These results mirror previous conceptualizations of violent extremism as resulting from a dynamic interaction among specific individual‐level vulnerabilities (i.e., cognitive and/or moral susceptibilities), various situational factors, and differential exposures to terrorism‐supportive settings and/or moral norms, . Unsurprisingly, lone‐actor terrorists were significantly more likely to express a desire to hurt others, and to have had access to a stockpile of weaponry.…”
Section: Discussionsupporting
confidence: 82%
“…Further follow‐up studies conceptualized such risk factors and indicators as relating to propensity, situation, and exposure (for a full discussion see Refs. ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To do so, the purposely built RAF, developed for the PRIME project, is adopted as theoretical guidance. The RAF has been applied to the modeling of various aspects of lone‐actor terrorist events (Bouhana, Corner, Gill, & Schuurman, ; Corner, Bouhana, & Gill, ; Schuurman, Bakker, Gill, & Bouhana, ), although it should be noted that nothing precludes the RAF from being applied to other types of offences. A detailed presentation of the RAF is beyond the scope of this article.…”
Section: Analytical Approachmentioning
confidence: 99%